The Attitude of the ’Ulama towards Political Authority: A Manuscript of the Late Safavid Period - Moussavi, Sayyed Ahmed Kazemi (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
The Attitude of the ’Ulama towards Political Authority: A Manuscript of the Late Safavid Period